MENGEDUKASI MASYARAKAT UNTUK MEMANFAATKAN WISATA AIK MENCERIT SEBAGAI SALAH SATU TEMPAT WISATA DI DESA PRINGGASELA DAN PEMANFAATAN MEDIA ONLINE SEBAGAI SARANA PEMASARAN PRODUK TENUN (DIGITAL MARKETING) - Firmansyah, Arya; Miranda, Tina Ayu; Handayani, Erra; Ziana, Lenny; Putri, Nuriati Alya; Aprianingsih, Aprianingsih; Aliashari, Nanang; Kamilaini, Kamilaini; Setiawati, Eka Aprilia; Jum’at, Muhammad (Universitas Mataram, 2023)
Pringgasela Village is a village in the Pringgasela District, East Lombok Regency, West Nusa Tenggara Province, Indonesia. Pringgasela village is surrounded by a large area of rice fields, so that most of the people there work as farmers and farm labourers, and some people make weaving crafts as an additional livelihood. Pringgasela Village itself has promising tourism potential, namely having various tourist areas (Mencrit River, Semporonan Waterfall, Goa Kopong Waterfall, Mayung Polak Waterfall, Aik Seleong Tourism Park, etc.) There is also woven fabric cultural tourism which is the main attraction the main village of Pringgasela. The condition of the area is still beautiful and natural so it has superior natural resources such as abundant water sources, fertile soil. Apart from the natural and land potential that Pringgasela Village has, there are several main problems in the village including the lack of tourists visiting, lack of public awareness of environmental cleanliness, facilities and infrastructure supporting tourism which are still inadequate. Therefore, with the 2022 Mataram University thematic KKN activities in Pringgasela Village, it is hoped that it can develop and exist the Pringgasela Village through work programs during KKN activities such as optimizing tourist and business spots, sustainable halls as a form of effort to provide understanding in handling school dropouts for children and Increasing interest in reading for elementary-junior high school age children, so that they get used to reading.